2013
DOI: 10.3892/or.2013.2548
|View full text |Cite
|
Sign up to set email alerts
|

miR-133a suppresses cell proliferation, migration and invasion in human lung cancer by targeting MMP-14

Abstract: Lung cancer is the leading cause of cancer‑related mortality worldwide. Over half of lung cancer cases are diagnosed after metastasis, for which the median survival time is approximately 8 months. microRNAs (miRNAs), which are a class of single‑stranded endogenous non‑coding RNAs, are likely to be involved in most biological processes. miR‑133 plays roles in cardiac development and disease, and recent studies showed that miR‑133 is downregulated in various human malignancies, such as bladder and lung cancer. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…MT1-MMP accelerated tumor migration and invasion by inducing the epithelial to mesenchymal transition in prostate and squamous cell carcinoma cells [9]. In addition, our previous study indicated that miR-133a suppresses cell proliferation, migration, and invasion in human lung cancer by targeting MMP-14 [10].…”
Section: Introductionmentioning
confidence: 90%
“…MT1-MMP accelerated tumor migration and invasion by inducing the epithelial to mesenchymal transition in prostate and squamous cell carcinoma cells [9]. In addition, our previous study indicated that miR-133a suppresses cell proliferation, migration, and invasion in human lung cancer by targeting MMP-14 [10].…”
Section: Introductionmentioning
confidence: 90%
“…It has been found that miR-9, miR-133a, and miR-24 bind to the 3′-UTR of MMP-14 (MT1-MMP) mRNA and directly block its translation. [24][25][26] On the other hand, downregulation of miR-199a-5p in a murine wound-healing model promoted angiogenesis in acute wounds via Ets-1 derepression and MMP-1 induction, both in vitro and in vivo. 27 As already mentioned, all members of the MMP family are released as an inactive form -proenzyme.…”
Section: Mmps Expression and Activationmentioning
confidence: 99%
“…We then examined the effect of PML on the expression of several genes important for cancer metastasis, including MMP2, MMP9, ITGB1 and MMP14. [36][37][38][39] We found that the mRNA expression of MMP2, but not of the other 3 genes, was significantly upregulated in response to PML knockdown ( Fig. 2A and Fig.…”
Section: Pml Suppressed Negfr-induced Mmp2 Expressionmentioning
confidence: 99%